Konstruksi Pengembangan Keilmuan Program Studi PAI pada Program Pascasarjana - Qomar, Mujamil (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2013)
The article explores the development construction of Islamic education at post graduate program both at PTAIN and PTAIS. The results show that the development construction of Islamic education at Islamic tertiary education need certain formula by considering all situation and condition related to the existence of the Islamic education. It is of paramount importance since they do contribute to the development construction of Islamic education. In addition, the emphasis of the construction should be reflected in any activity conducted by both leaturers and students.